Overview of the offshore financial services sector in the Caribbean and threats to its existence - Smith, Angella (CDB BridgetownBB, 1999)
Assesses the extent and economic significance of the offshore financial (OFS) sector in the Wider Caribbean (including Bermuda). Analyses international initiatives that might impinge upon this sector, their implications for the Caribbean and regional responses to these initiatives. Discusses prospects for the sector in the Caribbean and appropriate measures at the regional level to facilitate its growth and contribution to economic development.